Detection of Argyrotaenia sphaleropa Meyrick (Lepidoptera: Tortricidae) in cultivations of Persea americana Mill. - Valverde Rodríguez, Agustina; Campos Albornoz, Miltao Edelio; Pérez Velasquez, Neccy Anel; Gonzales Pariona, Fernando Jeremías (Revista Mexicana de Ciencias Agrícolas, 2021)
The Germplasm Bank of 22 varieties of avocado is located at the Olericultural Fruit Research Center of the Faculty of Agricultural Sciences of the Hermilio Valdizán National University. During the period March-August 2019, the presence of the species Argyrotaenia sphaleropa Meyrick was detected attacking the avocado cultivation. Fruits were sampled describing the characteristics of the damage. Likewise, the larvae and pupae found were transferred to the laboratory for breeding and their morphological description based on the dichotomous key of the order. It was observed that the larvae began their feeding with irregular scrapes of the epicarp and could affect up to the mesocarp of the fruit and, as they passed, they left white droppings, joined the leaves and fruits together with silk threads, serving as shelter for the larvae for the pupal process and subsequent development of the adult.
Keywords: Argyrotaenia sphaleropa; avocado pest; silk threads